Cryogenic and Laser Photoexcitation Studies Identify Multiple Roles for Active Site Residues in the Light-driven Enzyme Protochlorophyllide Oxidoreductase - Menon, Binuraj R. K. (American Society for Biochemistry and Molecular Biology, 2009)
The light-activated enzyme NADPH-protochlorophyllide oxidoreductase (POR) catalyzes the trans addition of hydrogen across the C-17–C-18 double bond of protochlorophyllide (Pchlide), a key step in chlorophyll biosynthesis. Similar to other members of the short chain alcohol dehydrogenase/reductase family of enzymes, POR contains a conserved Tyr and Lys residue in the enzyme active site, which are implicated in a proposed reaction mechanism involving proton transfer from the Tyr hydoxyl group to Pchlide. We have analyzed a number of POR variant enzymes altered in these conserved residues using a combination of steady-state turnover, laser photoexcitation studies, and low temperature fluorescence spectroscopy. None of the mutations completely abolished catalytic activity. We demonstrate their importance to catalysis by defining multiple roles in the overall reaction pathway. Mutation of either residue impairs formation of the ground state ternary enzyme-substrate complex, pointing to a key role in substrate binding. By analyzing the most active variant (Y193F), we show that Tyr-193 participates in proton transfer to Pchlide and stabilizes the Pchlide excited state, enabling hydride transfer from NADPH to Pchilde. Thus, in addition to confirming the probable identity of the proton donor in Pchlide reduction, our work defines additional roles for these residues in facilitating hydride transfer through stabilization of the ground and excited states of the ternary enzyme complex.